2023
DOI: 10.1097/hc9.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary care for patients with HCC: a systematic review and meta-analysis

Abstract: Background: Given the complexity of managing HCC, professional society guidelines advocate multidisciplinary care (MDC) for patients with HCC. However, implementation of MDC programs requires a significant investment of time and resources. We conducted a systematic review and meta-analysis to enumerate potential benefits of MDC for patients with HCC. Methods: We conducted a search of the PubMed/MEDLINE and EMBASE databases and national conference abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…These data reinforce that screening is only the first step in the cancer care continuum, and patients with early-stage detection must undergo timely curative treatment to have improved survival . Efforts are needed to promote patients receiving high-quality care at multidisciplinary, high-volume settings to reduce issues regarding underuse of curative treatments …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These data reinforce that screening is only the first step in the cancer care continuum, and patients with early-stage detection must undergo timely curative treatment to have improved survival . Efforts are needed to promote patients receiving high-quality care at multidisciplinary, high-volume settings to reduce issues regarding underuse of curative treatments …”
Section: Discussionmentioning
confidence: 89%
“… 34 , 35 , 36 Efforts are needed to promote patients receiving high-quality care at multidisciplinary, high-volume settings to reduce issues regarding underuse of curative treatments. 34 , 37 , 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a comprehensive meta-analysis of 12 studies including 15,365 HCC patients suggested that MDT is associated with improved OS, with a HR of 0.63 (95% confidence interval [CI], 0.45-0.88), highlighting the potential benefits of MDT in managing HCC. 19 Nonetheless, the direct association between MDT care and an increased chance of receiving curative treatments was not statistically significant (risk ratio, 1.60; 95% CI, 0.89-2.89). It is important to note that the study was limited by high heterogeneity and potential referral bias.…”
Section: The Role and Efficacy Of Mdt In Hcc Managementmentioning
confidence: 89%
“…Interestingly, the survival benefit of a multidisciplinary approach has been demonstrated in several studies, including a meta-analysis involving more than 15,000 patients, 69 leading to different guidelines for recommending this approach.…”
Section: A Paradigm Shift In Staging Systemsmentioning
confidence: 99%